Studi Komparasi Ajaran Kanda Pat Padepokan Sastra Jendra Dan Kanda Pat Perguruan Seruling Dewata - Ida Bagus Benny Surya Adi Pramana (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
The flute college of the godsis one of the oldest martial arts colleges in Indonesia in addition to teaching martial arts and internal energy. The flute college of the gods also teaches the science of Hindu religion, according to the legacy of Yogi and Yogini of ancient times, who had studied at The flute college of the gods. This college was originally, one of the branches of college months. Where in ancient times, there are two major Silat colleges on the island of Bali is the university of the moon and the university of the sun. Apart from the flute college of the gods there is also the college Kanda Pat Bali which is engaged in meditation, medicine and enlightenment.